Faktor – Faktor yang Berpengaruh Terhadap Kinerja Perusahaan - Angelia Sundari; Sufiyati (Economic Reviews Journal, 2024)
This research aims to explore the impact of company size, earnings management and audit committee variables on the performance of a company in the non-cyclical consumer sector that has been listed on the Indonesia Stock Exchange (BEI) forum between 2018 and 2022. The process carried out in The following research uses the Nonprobability Sampling method to determine the sample and Purposive Sampling for sample design, in accordance with the specified criteria. Data analysis in this research used IBM SPSS version 25 software. The research shows that company size has no significant effect on company performance. Management also has no significant effect on company performance, while the audit committee has a significant negative impact on company performance variables. These findings provide guidance for practitioners to increase the effectiveness of their steps in an effort to improve company performance, with the hope of providing a positive impact on the growth and continuity of their business.